On reducing the effects of clipping in an enhanced Orthogonal Frequency Division Multiplexing system - Wan Hafiza, Wan Hassan (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.